Strauss’ and Lions’ Type Results in BV(RN) with an Application to an 1-Laplacian Problem - Figueiredo, Giovany M.; Pimenta, Marcos T. O. [UNESP] (Springer Nature, 2018)
In this work we state and prove versions of some classical results, in the framework of functionals defined in the space of functions of bounded variation in RN. More precisely, we present versions of the Radial Lemma of Strauss, the compactness of the embeddings of the space of radially symmetric functions of BV (RN) in some Lebesgue spaces and also a version of the Lions Lemma, proved in his celebrated paper of 1984. As an application, we get existence of a nontrivial bounded variation solution of a quasilinear elliptic problem involving the 1−Laplacian operator in RN, which has the lowest energy among all the radial ones. This seems to be one of the very first works dealing with stationary problems involving this operator in the whole space.
Keywords: 1-Laplacian operator; Bounded variation functions; compactness with symmetry